2022
DOI: 10.1186/s12891-022-06027-9
|View full text |Cite
|
Sign up to set email alerts
|

The association of biomarkers with pain and function in acute and subacute low back pain: a secondary analysis of an RCT

Abstract: Background Low back pain (LBP) is a common musculoskeletal condition and a major cause of disability worldwide. Previous studies have found associations of biomarkers with pain and pain-related disability in LBP patients. This study aimed to explore the association between serum biomarkers and pain and disability in patients with acute or subacute axial LBP. Methods This study was ancillary to a parent randomized controlled trial. Enrolled particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(50 reference statements)
0
0
0
10
Order By: Relevance
“…Two reviews [ 86 , 175 ] offer consideration of the three available early original research studies (including Brennan et al [ 318 ] which is not specifically included within the present dataset since it was published in 1991) and discuss limited evidence that substance P increases after spinal manipulation. Of the available original research studies meeting our inclusion criteria, two describe positive immediate and short-term changes in substance P after spinal manipulation [ 176 , 177 ], and one paper was identified in our search that describes no change in substance P [ 92 ]. Further research will be necessary to clarify this apparent discrepancy; however, the results observed in the two former studies suggest that examination of changes in substance P levels in response to chiropractic care merits further consideration.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Two reviews [ 86 , 175 ] offer consideration of the three available early original research studies (including Brennan et al [ 318 ] which is not specifically included within the present dataset since it was published in 1991) and discuss limited evidence that substance P increases after spinal manipulation. Of the available original research studies meeting our inclusion criteria, two describe positive immediate and short-term changes in substance P after spinal manipulation [ 176 , 177 ], and one paper was identified in our search that describes no change in substance P [ 92 ]. Further research will be necessary to clarify this apparent discrepancy; however, the results observed in the two former studies suggest that examination of changes in substance P levels in response to chiropractic care merits further consideration.…”
Section: Reviewmentioning
confidence: 99%
“…The impact of chiropractic care on substance P has been examined in four reports [86,[175][176][177]. Two reviews [86,175] offer consideration of the three available early original research studies (including Brennan et al [318] which is not specifically included within the present dataset since it was published in 1991) and discuss limited evidence that substance P increases after spinal manipulation.…”
Section: Substance Pmentioning
confidence: 99%
“…Por fim, um estudo clínico randomizado recente apontou outras substâncias que podem ser consideradas como um potencial marcador inflamatório da DLC tais como o neuropeptídeo Y (NPY), a molécula de adesão E-selectina e a vitamina D (ENRICO et al, 2022). A vitamina D apresenta um importante papel no metabolismo do Ca2+ e na regulação imunológica, sendo encontrado em baixas concentrações em indivíduos com maior intensidade de dor referida (ZADRO et al, 2017).…”
Section: Marcadores Inflamatórios Na Dor Lombar Crônicaunclassified
“…A vitamina D apresenta um importante papel no metabolismo do Ca2+ e na regulação imunológica, sendo encontrado em baixas concentrações em indivíduos com maior intensidade de dor referida (ZADRO et al, 2017). Apesar de não haver clareza na literatura científica que evidencie essa relação, o NPY e a E-selectina estão associados à condições de dor crônica e demonstraram-se elevados em indivíduos com DLC ( DIAZ-DELCASTILLO, WOLDBYE, HEEGAARD, 2018;ENRICO et al, 2022).…”
Section: Marcadores Inflamatórios Na Dor Lombar Crônicaunclassified